In silico evidence for the species-specific conservation of mosquito retroposons: implications as a molecular biomarker - Byarugaba, Wilson; Kajumbula, Henry; Wayengera, Misaki (Theoretical Biology and Medical Modelling, 2009)
Mosquitoes are the transmissive vectors for several infectious pathogens that affect man. However, the control of mosquitoes through insecticide and pesticide spraying has proved difficult in the past. We hypothesized that, by virtue of their reported vertical inheritance among mosquitoes, group II introns – a class of small coding ribonucleic acids (scRNAs) – may form a potential species-specific biomarker. Structurally, introns are a six-moiety complex. Depending on the function of the protein encoded within the IV moiety, the highly mobile class of group II introns or retroposons is sub-divided into two: Restriction Endonuclease (REase)-like and Apurinic aPyramydinic Endonuclease (APE)-like. REase-like retroposons are thought to be the ancestors of APE retroposons. Our aim in this study was to find evidence for the highly species-specific conservation of the APE subclass of mosquito retroposons.
Keywords: Silico evidence; Species-specific conservation; Mosquito retroposons; Molecular biomarker